Left Atrial Remodeling After Anterior STEMI: A Randomized Trial of Continuous High-Intensity Versus Moderate-Intensity Aerobic Training in Post-PCI Cardiac Rehabilitation - Ahmed Kadry Araquib; Ahmed Hossam Abdelnaby Hammad; Tarek Khairy Abdeldayem; Ramy Raymond Elias (International Journal of the Cardiovascular Academy, 2025)
Background and Aim: Myocardial infarction (MI) triggers adverse structural and functional cardiac remodeling. While moderate-intensity exercise-based cardiac rehabilitation (CR) improves recovery, emerging evidence suggests higher-intensity regimens may yield greater benefits. Although high-intensity interval training has demonstrated safety and efficacy in cardiac populations, the impact of high-intensity continuous aerobic training (HICT) on left atrial (LA) mechanics post-primary percutaneous coronary intervention (PCI) for anterior wall ST-segment elevation MI (STEMI) remains underexplored. This study aims to investigate the impact of HICT versus moderate-intensity continuous training (MICT) on LA mechanics in patients post-primary PCI for anterior STEMI. Materials and Methods: In a single-center randomized controlled trial at Aim Shams University Hospital, 60 adults 1-month post-primary PCI for anterior STEMI were randomized to 6 weeks of CR involving either high-intensity continuous training [HICT; 80-90% peak heart rate (HR)] or (MICT; 50-70% peak HR). Participants completed 18 treadmill sessions (3/week). Diastolic function and LA mechanics (reservoir, conduit, contractile strains) were assessed via two-dimensional speckle-tracking echocardiography pre- and post-intervention. Results: This study examined patients with a mean age of 51.82 years, predominantly male (91.7%). Both the HICT group and the comparator group exhibited improvements in LA mechanics and diastolic function, though intergroup differences were statistically non-significant. HICT group demonstrated numerically greater gains in LA reservoir strain (5.67±4.39% vs. 3.80±3.32%, P = 0.115) and LA contractile strain (-2.93±4.27% vs.-1.33±3.74%, P = 0.110). Similarly, reductions in diastolic indices were comparable between groups: E/A (0.14±0.12 vs. -0.14±0.14, P = 0.927) and E/E’ (-0.25±0.16 vs. -0.30±0.34, P = 0.568). While trends favored HICT, no outcome reached statistical significance, suggesting comparable efficacy between interventions. Conclusion: HICT and MICT show comparable safety and efficacy in enhancing cardiac function, suggesting exercise intensity may be tailored to patient preference or tolerance.